2015
DOI: 10.1371/journal.pone.0125487
|View full text |Cite
|
Sign up to set email alerts
|

The General Amino Acid Permease FfGap1 of Fusarium fujikuroi Is Sorted to the Vacuole in a Nitrogen-Dependent, but Npr1 Kinase-Independent Manner

Abstract: The rice pathogenic fungus Fusarium fujikuroi is well known for the production of a broad spectrum of secondary metabolites (SMs) such as gibberellic acids (GAs), mycotoxins and pigments. The biosynthesis of most of these SMs strictly depends on nitrogen availability and of the activity of permeases of nitrogen sources, e.g. the ammonium and amino acid permeases. One of the three ammonium permeases, MepB, was recently shown to act not only as a transporter but also as a nitrogen sensor affecting the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…Whereas TORC1 inhibition causes global up-regulation of Rsp5 activity ( Iesmantavicius et al, 2014 ) and TORC1 activity controls trafficking of nutrient transporters, opposing modes of TORC1 control over individual transporters have been described. Some stimuli that activate TORC1 cause amino acid transporters such as Can1, Mup1, and Gap1 to traffic to the vacuole through activation of particular arrestin-related substrate-adaptors of the Rsp5 ligase ( Schmidt et al, 1998 ; MacGurn et al, 2011 ; Martín et al, 2011 ; Merhi and André, 2012 ; Crapeau et al, 2014 ; Pfannmüller et al, 2015 ). This mechanism does not explain how leucine starvation, which would inactivate TORC1, results in rapid withdrawal of transporters from the cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas TORC1 inhibition causes global up-regulation of Rsp5 activity ( Iesmantavicius et al, 2014 ) and TORC1 activity controls trafficking of nutrient transporters, opposing modes of TORC1 control over individual transporters have been described. Some stimuli that activate TORC1 cause amino acid transporters such as Can1, Mup1, and Gap1 to traffic to the vacuole through activation of particular arrestin-related substrate-adaptors of the Rsp5 ligase ( Schmidt et al, 1998 ; MacGurn et al, 2011 ; Martín et al, 2011 ; Merhi and André, 2012 ; Crapeau et al, 2014 ; Pfannmüller et al, 2015 ). This mechanism does not explain how leucine starvation, which would inactivate TORC1, results in rapid withdrawal of transporters from the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…TORC1 has been shown to influence this process in part by regulating the activity of particular ubiquitin (Ub)-ligase complexes. However, various interrelated regulatory pathways that connect TORC1 activity to ubiquitination do not adequately explain how global control of their trafficking is mediated by nutrient stress, such as nitrogen limitation ( Schmidt et al, 1998 ; MacGurn et al, 2011 ; Martín et al, 2011 ; Merhi and André, 2012 ; Crapeau et al, 2014 ; Pfannmüller et al, 2015 ). One aspect that remains unclear is the extent to which metabolic cues may control flux through the trafficking pathways that convey proteins back to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also conceivable that the distinct functions carried out by Npr1 in Saccharomyces cerevisiae could be supported by distinct Npr1-like, or even distinct kinases, in other species. For instance, in collaboration with the team of Bettina Tudzynski, we recently showed that the expression of at least one of the Fusarium fujikuroi Npr1-like proteins confers growth on ammonium to the Saccharomyces cerevisiae npr1 mutant while being unable to mediate Mep2 phosphorylation [ 65 ]. These data suggest that the Fusarium kinase is able to protect yeast Mep1 and/or Mep3 against Amu1-mediated inactivation while being unable to control Mep2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent-protein tags are common tools to monitor the protein localization. It has been extensively practiced in the research of F. fujikuroi (Studt et al, 2013b;Pfannmuller et al, 2015). Michielse et al (2014) tagged the GATA transcription factors AreA and AreB with GFP and RFP respectively to track their cytosolic or nucleic localization.…”
Section: Fluorescent Proteinsmentioning
confidence: 99%